Analysis of Cultural Dimensions in Career Development of West Java Police Personnel - Riskawati Riskawati; I Gede Nyoman Bratasena; Rio Adhikara; Novi Indah Earlyanti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyze the cultural dimensions of West Java Police personnel, focusing on their career development, with particular attention to the influence of masculine-feminine cultural dimensions on the career orientations of male and female officers. Research Methodology: A qualitative research approach was employed, utilizing ethnographic methods. Data were collected through surveys, interviews, and document analysis. This study focused on the personnel of Polda Jawa Barat, examining the cultural dimension of masculine-feminine through both primary and secondary data. Results: The findings revealed that male officers exhibited a feminine cultural orientation, while female officers demonstrated a masculine cultural orientation. Masculine culture is characterized by assertiveness, competitiveness, ambition, and power, whereas feminine culture emphasizes relationships and quality of life. Conclusions: The study concludes that cultural dimensions significantly impact career development in the police force. Male officers tend to be more career-driven, while female officers often face external cultural barriers despite having a strong masculine orientation. Limitations: The study was limited by time constraints and the vast geographical area of Polda Jawa Barat, which affected the data collection scope. Additionally, this study focused primarily on career-oriented dimensions, excluding other aspects of police personnel culture. Contributions: This research contributes to the understanding of the role of cultural dimensions in career development, particularly in the context of gender within the police force. This study provides insights into improving career development programs for female officers.